The new ocean : the fate of life in a changing sea - Barnard, Bryn (Alfred A. Knopf, 2017)
Presents the fates of six ocean dwellers, jellyfish, orcas, sea turtles, tuna, corals, and blue-green algae, and describes how each of them is affected by human actions which are making the ocean warmer and more polluted.